Cover Picture: Singlet Fission in Carbene‐Derived Diradicaloids (Angew. Chem. Int. Ed. 20/2020). Issue 20 (14th April 2020) - Ullrich, Tobias; Pinter, Piermaria; Messelberger, Julian; Haines, Philipp; Kaur, Ramandeep; Hansmann, Max M.; Munz, Dominik; Guldi, Dirk M.
Abstract : The entanglement of states is a fascinating result of quantum physics. In the singlet fission process, a pair of chromophores in the S1 S0 state evolves into the spin‐entangled T1 T1 state. While most studies on singlet fission have been restricted to alternated hydrocarbons, the potential of diradicaloids as singlet fission chromophores has remained largely unexplored. In their Research Article on page 7906, M. M. Hansmann, D. Munz, D. M. Guldi et al. present a new family of carbene‐derived diradicaloids undergoing this photophysical process. The entangled T1 T1 state is depicted as two climbers holding hands.